The Role of Regional Original Revenue and General Allocation Funds as a Source of Revenue in the Regional Revenue and Expenditure Budget of the East Java Provincial Government - Andri Purdiono; Ika Devy Pramudiana; Eny Haryati; Sapto Pramono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe and analyze: the role of PAD and DAU as a source of revenue in APBD financing in East Java Province and how the East Java Provincial Regional Government efforts to increase PAD through Regional Original Tax. The data analysis technique uses the technique developed by McNabb (2002), namely Grouping the data according to key constructs, Identifying bases for interpretation, Developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that the Role of Regional Original Revenue in the Regional Budget in the East Java Provincial Government is very high. The dependence of the East Java Provincial Government on the Central Government is relatively low. This is evidenced by the magnitude of the PAD value to the APBD around 72%. DAU's contribution to the APBD is quite high, in 2024 it will reach 82%. This indicates that the local government of the East Java Provincial Government uses DAU more than PAD for Regional Expenditure. This means that there is fiscal dependence on the central government and provincial governments. In general, the policy of increasing Regional Original Revenue from the Tax sector carried out by the East Java Provincial Government includes Synergy between the Provincial Government and Regency/City Government, Innovation in tax payment services, Re-data collection of taxpayers, Cooperation with the private sector and NGOs, Improvement of tax management management. The East Java Provincial Government together with the Regional Governments of Regencies/Cities throughout East Java collaborate in the synergy of regional tax collection and regional tax options. The goal is to create effective regional financial management by prioritizing synergy in optimizing the increase in Regional Original Revenue (PAD: Pendapatan Asli Daerah) to encourage fiscal independence in the regions.